POTENSI DAYA TARIK DAN PERSEPSI PENGUNJUNG TERHADAP OBJEK WISATA PANTAI WAMSOBA DESA WALLI KABUPATEN BURU SELATAN. - Rusmin Nurlatu; Billy B Seipalla (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The perception of visitors to the objects and tourist attractions of Wamsoba beach, wali village, Namrole district, South Buru Regency is a research conducted with the aim of knowing the potential tourist attraction and visitor perceptions of the existing facilities and infrastructure on Wamsoba beach. , in this study the data collection methods used were in the form of operational area analysis (ADO), direct field observation, distribution of questionnaires / interviews and literature study. Analysis of research data using the operational area analysis method (ADO), and qualitative descriptive analysis to answer research based on information obtained from field observations. From the research results, it can be seen that the assessment related to tourist attractions meets the criteria value to be feasible to develop.